2019
DOI: 10.17275/per.19.4.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Lesson Study as a Tool to Improve Students' Learning and Professional Development of Teachers

Abstract: Continuous professional development is a process that requires constant and active learning for a teacher throughout his/her professional life. In this process, teachers are expected to perform activities aiming at increasing both their professional development and the quality of teaching within the classroom. One of these is lesson study. This study examined the effect of the lesson study as a tool to improve professional development of teachers, as well as student learning. Case study, one of the qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(30 reference statements)
2
8
0
3
Order By: Relevance
“…Teachers A, G, F, and I believed that learners in the implemented LS are made thinkers, participative, keener, and analytical due to the activities that they are exposed with. Similar phenomenon is observed by various authors who implemented LS [1], [6], [7], [13], [14], [25]. Iksan, Zakaria, and Daud [1] emphasized the role of social interaction, while Butun [7], Bayram and Canaran [13] suggested that teachers should come with a tangible research plan addressing the observed strengths and weaknesses of LS in their research locale.…”
Section: Scheming Avenues For Critical Thinkingsupporting
confidence: 74%
See 1 more Smart Citation
“…Teachers A, G, F, and I believed that learners in the implemented LS are made thinkers, participative, keener, and analytical due to the activities that they are exposed with. Similar phenomenon is observed by various authors who implemented LS [1], [6], [7], [13], [14], [25]. Iksan, Zakaria, and Daud [1] emphasized the role of social interaction, while Butun [7], Bayram and Canaran [13] suggested that teachers should come with a tangible research plan addressing the observed strengths and weaknesses of LS in their research locale.…”
Section: Scheming Avenues For Critical Thinkingsupporting
confidence: 74%
“…Usually, the group is composed of 3-5 member teachers who are teaching similar fields under the supervision of a senior or a seasoned teacher in a specified field of learning [3], [10], [11]. The implementation of LS in Japan yielded significant results and earned positive feedback in the academic communities around the world [7], [12]- [14]. Aptly, Philippines is one of the countries that looked into the potentialities of conducting LS.…”
Section: Introductionmentioning
confidence: 99%
“…He found out that the model enabled teachers to apply different teaching methods, collaborate with each other, and exchange opinions. Özdemir (2019) also highlighted that especially low performing students, and students with difficulties in self-expression benefited from the lesson study experience.…”
Section: Introductionmentioning
confidence: 99%
“…Bahçivan’s (2017) study with pre-service science teachers showed that lesson study broadened teacher knowledge by positively affecting their subject as well as pedagogical knowledge. In his study conducted with two primary school teachers, Özdemir (2019) investigated how lesson study improved the PD of teachers as well as student learning. He found out that the model enabled teachers to apply different teaching methods, collaborate with each other, and exchange opinions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, collaborative professional learning, professional communities, communities of practice and many other terms have been used in the educational literature to refer to the reform models of PD. Studies suggest that reform models expose teachers to the practices of one another and allow them to share their experience which results in not only broadening their knowledge (Kanellopoulou and Darra, 2018) but also overcoming the culture of isolation prevailing in many schools ( € Ozdemir, 2019). These models are further supported by those academics who show a close positive relation between reform models of learning and student learning outcomes (Darling-Hammond, 2004;Opfer and Pedder, 2011a).…”
Section: Reform Modelsmentioning
confidence: 99%